Effect of phosphorus and liming sources on rice (Oryza sativa) grain yield under transplanted conditions - MUTANAL, S M; KUMAR, PRASAD; JOSHI, V R; PRABHAKAR, A S; MANNIKERI, I M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during rainyÂ season (kharif) 1992, 1993 and 1994 at Sirsi (Hillzone 9) of Karnataka to study the effect of lime and phosphorus sources on grain yield of rice under transplanted conditions. The experiment consisted’of 6 sources of phosphorus and 2 levels of lime. Application oflime @500 kg/ha had significantly increased yield compared with without lime (control). The combination of rockÂ phosphate + diammonium phosphate (50:50) had significantly increased yield (5 205 kg/ha) and was on par with diammonium phosphate alone (4 790 kg/ha) than rock phosphate (4 690 kg/ha). Net profit (Rs 7 114/ha) was higher in rock phosphate + diammonium phosphate (50:50) followed by the diammonium phosphate (Rs 5 920/ha) and west was in single superphoshate (Rs 4 651/ha).